Protective effects of Lactobacillus rhamnosus GG supernatant on metabolic associated fatty liver disease through intestinal barrier restoration and regulation of the regenerating gene 3γ - Wang, Si-Pu; Ba, Ling; Lv, Xin-Rui; Qi, Ya-Xin; Wang, Xu; Zhang, Jie; Xu, Xin (Frontiers in Microbiology, 2025)
ObjectiveThe regenerating gene 3γ (Reg IIIγ) protein, a key antimicrobial peptide, is essential for maintaining intestinal barrier homeostasis and host defense. Its expression is impaired in metabolic-associated fatty liver disease (MAFLD), particularly under high-fat diet (HFD) conditions, contributing to barrier dysfunction. Given evidence that probiotic-derived components can modulate Reg IIIγ, this study aimed to evaluate the effects of Lactobacillus rhamnosus GG supernatant (LGGs) on Reg IIIγ expression, their impact on intestinal barrier function, and their therapeutic potential in mitigating MAFLD, while elucidating the underlying mechanisms involving the TLR2/MyD88/pSTAT3 signaling pathway.MethodsSix-week-old C57BL/6 J mice were randomly assigned to four groups: standard diet with phosphate-buffered saline (PBS), standard diet with LGGs, high-fat diet (HFD) with PBS, and HFD with LGG. The expression of intestinal Reg IIIγ, changes in intestinal microbiota, and intestinal permeability were analyzed using quantitative PCR (qPCR) and western blot techniques. In vitro experiments involved assessing HIP/PAP expression in Caco-2 cell lines following stimulation with LGG supernatants, using qPCR and western blot. Additionally, siRNA transfection of Caco-2 cells was used to examine the MyD88/pSTAT3 signaling pathway.ResultsHFD impaired the intestinal barrier in mice. However, oral administration of LGG significantly enhanced the expression of Reg IIIγ in the intestinal mucosa compared to control groups. This intervention notably improved intestinal barrier function, modulated the composition of intestinal microbiota, and mitigated MAFLD. Furthermore, an inverse correlation was observed between intestinal permeability and Reg IIIγ expression. In vitro, stimulation of Caco-2 cells with LGG led to a significant upregulation of HIP/PAP protein expression, mediated through the MyD88/pSTAT3 signaling pathway.ConclusionLGG supernatant enhances intestinal Reg IIIγ expression through the MyD88/pSTAT3 signaling pathway, thereby contributing to the protection of intestinal barrier function and alleviation of MAFLD.